The Effect of Self-Esteem on Fear Of Negative Evaluation in Students - Auliannisa, Siti Hajar; Firdaus, Faradillah; Fakhri, Nur Fitriany (Polteknik Ilmu Pemasyarakatan, 2024)
Fear of negative evaluation refers to the fear experienced by individuals, stemming from concerns that others may perceive or judge them negatively. One influential factor affecting this fear is self-esteem. This research aims to determine the impact of self-esteem on students' fear of negative evaluation. This research uses ordinal regression analysis techniques. The respondents for this study consisted of 304 students selected through accidental sampling techniques. The research findings reveal a significant negative correlation between self-esteem and fear of negative evaluation in students (r = -9,572, p = 0.00 < 0.05), indicating that higher self-esteem scores are associated with lower levels of fear of negative evaluation among students. Future researchers are encouraged to explore the correlation between fear of negative evaluation and other variables to identify additional factors that may have a more substantial impact on fear of negative evaluation. Additionally, employing alternative methods such as experimental approaches could provide direct insights into the implications of enhancing self-esteem in reducing fear of negative evaluation. The implication of this research is an understanding of the need for students to increase their self-esteem and overcome the fear of negative evaluation so that they can better achieve their academic and social potential.